SPE Oil and Gas India Conference and Exhibition 2010
DOI: 10.2118/128848-ms
|View full text |Cite
|
Sign up to set email alerts
|

Immiscible Hydrocarbon Wag: Laboratory to Field

Abstract: A sandstone reservoir at a depth of 2800 m in a western India onshore field contains highly under saturated light oil of 470 API with viscosity of 0.2 cp. The reservoir has a permeability ranging 50 to 300 md and high temperature of around 130 Deg C. It is exploited by supplementing the partial water drive with water injection. Water injection was initiated in the early part of its producing life and has recovered more than 30% of OIIP. Meanwhile, availability of natural gas from deeper reservoirs in the field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…The results of the pilot were favorable, with a 5.7 fold increase in oil production and an average decreased water cut from 78% to 68%. Whereas the laboratory studies indicate an IWAG incremental recovery of 14.5% OOIP, the pilot simulation studies indicate a 9.5 % OOIP incremental recovery (Ramachandran et al, 2010. Baojun and Cai, Y, 1997 was a report titled ЉPilot Test of Water alternating Gas Injection in Heterogeneous Thick Reservoirs of Positive Rhythm Sedimentation of Daqing Oil Field.Љ The authors reported a 3% incremental recovery from the IWAG pilot and a predicted 8% incremental ultimate recovery.…”
Section: E Field Offshore West Africamentioning
confidence: 99%
“…The results of the pilot were favorable, with a 5.7 fold increase in oil production and an average decreased water cut from 78% to 68%. Whereas the laboratory studies indicate an IWAG incremental recovery of 14.5% OOIP, the pilot simulation studies indicate a 9.5 % OOIP incremental recovery (Ramachandran et al, 2010. Baojun and Cai, Y, 1997 was a report titled ЉPilot Test of Water alternating Gas Injection in Heterogeneous Thick Reservoirs of Positive Rhythm Sedimentation of Daqing Oil Field.Љ The authors reported a 3% incremental recovery from the IWAG pilot and a predicted 8% incremental ultimate recovery.…”
Section: E Field Offshore West Africamentioning
confidence: 99%
“…Thermal method comprises approximately 70 % of all EOR techniques followed in India, which includes 50 % of in situ combustion (Ramachandran et al 2010). In many heavy oilfields in onshore assets operated by ONGC, in situ combustion has been used.…”
Section: Eor Techniques In Indian Reservoirsmentioning
confidence: 99%
“…Simulation of WAG injection process carried out for the pilot area indicated that WAG injection could yield in approximately 9.5 % incremental recovery over the base case of water injection [18]. Water injection was initiated at early life of the reservoir and has recovered about 30% of OIIP.…”
Section: Study Of 10 Years Wag Injection In Gullfask Field Conducted mentioning
confidence: 99%